A Test of Efficiency of the Closed-end Mutual Funds Market in China - Yang, Mingming (2006)
The aim of this paper is to test the efficiency of the closed-end of mutual funds market in China. It presents the performance of the closed-end mutual funds during the period from 2nd, Jan. 2003 to 31st, Dec. 2005. The paper first introduces the theoretical basis for this study, such as Markowitz Portfolio Selection theory, CAPM theory, Random walk theory and EMH theory. And then conventional measures, JensenÃÂÃÂÃÂÃÂ¢ÃÂÃ¢ÂÂÃÂÃ¢ÂÂ¬ÃÂÃ¢ÂÂÃÂÃ¢ÂÂ¢s Alpha, Treynor Index and Sharpe Ratio, are chosen to evaluate the performance of sample data. The sample in this study is all of the 54 closed-end mutual funds set up in China.